Pengaruh penambahan Silikon pada remelting piston motor bekas menggunakan tungku induksi terhadap kekuatan tarik dan kekerasan - Eko Nugroho; Eko Budiyanto; Aji Dawam Firdaus (Universitas Muhammadiyah Metro, 2021)
Aluminum is one of the most widely used non-ferrous metals in industry and engineering because of its light weight and resistance to corrosion. The purpose of this study is to change the waste of used motor pistons using an induction furnace by recycling or remelting the material and adding a mixture of silicon with variations of 8%, 10% and 12% to improve its mechanical properties. In this research, I used the main furnace for the smelting. The results of this study in the tensile test showed that the strength and wear strength increased with the addition of silicon elements but became brittle and stiff this happened because the value of the elastic modulus decreased with the addition of silkon elements, namely at 12% at 1.06 N/mmÂ² and at a variation of 8 % of 1.13 N/mmÂ². In the hardness test, it was found that the addition of silicon to aluminum with variations of 8%, 10% and 12% increased the hardness of the material.